y=3/5x-5/3

Simple and best practice solution for y=3/5x-5/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=3/5x-5/3 equation:


x in (-oo:+oo)

y = (3/5)*x-(5/3) // - (3/5)*x-(5/3)

y-((3/5)*x)+5/3 = 0

(-3/5)*x+y+5/3 = 0

y-3/5*x+5/3 = 0 // - y+5/3

-3/5*x = -(y+5/3) // : -3/5

x = (-(y+5/3))/(-3/5)

x = 5/3*(y+5/3)

x = 5/3*(y+5/3)

See similar equations:

| (3y-5z)(5y-6Z)= | | 12k^2+8k= | | x^3+3x^2-21x+7=0 | | 7x-9+6x=-9 | | 0.54x=-1.89 | | 0.54=-1.89 | | h=-16t^2+240t+1600 | | 8+4lnx=28 | | f(x)=2x^2-4x-1 | | (x+5)+(3x)+(x)=180 | | 30=x+2x+6x+3 | | 5+x=-5x+59 | | 3n^2+15n-150=0 | | 1+x+2x^3+3x^5=0 | | X=-5y+46 | | -2t+3b+4t= | | Log(x)=3.6 | | 267=5x+4(6x+16) | | 2667=5x+4(6x+16) | | x+y-z=n | | 45/12=5y | | 12X-12=18*14X | | 6x^2-2x-5= | | -34=3x-2(4x+32) | | 2X+2-3.2X=8 | | 3x+7x-6=0 | | y=-0.05x^2+100x-12000 | | 4=-4x^3 | | 2=1/4x^2 | | -1127=-7(-11x-26) | | 4x-30=x+50 | | F(-2)=0.5(2-(-2)) |

Equations solver categories